Formulasi Trigonometri Dalam Pembuatan Software Penentuan Arah Kiblat berbasis Visual Basic - Mustafa Syukur; Muhammad Hasan Basri (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2019)
The science of Falak is basically divided into two types, namely the science of Falak Ilmiy, and the science of Falak Amaliy. The science of Falak discussing the direction of Qibla is basically calculating the amount of angles flanked by meridian lines that pass through a place that is called the Qibla direction with a large circle passing through the relevant place and the Kaaba, and calculating what time the sun cuts the path to the Kaaba. The problem that arises is not everyone is able to calculate the correct direction about the Qibla direction but instead uses a range of directions. It is possible to make an application program for determining the direction of Qibla and others so that it can be used for the general public and is easy to apply. This research helps how to calculate the direction of Qibla and how to make and apply the software of Qibla direction determination using visual basic. The results of this study can be used as a reference in solving various cases of physical analysis in various aspects related to other astronomy.